2022
DOI: 10.3390/ijerph19159716
|View full text |Cite
|
Sign up to set email alerts
|

Family Dysfunction and Cyberchondria among Chinese Adolescents: A Moderated Mediation Model

Abstract: Cyberchondria has become a severe health problem and a significant public concern. In addition to the impacts that cyberchondria involves, individual psychological and behavioral factors have been identified. However, the role of family function and the mediating and moderating mechanisms underlying these relations are not understood well, especially among adolescents. Based on family functioning and cognitive-behavioral theory, this study sought to examine whether family dysfunction was associated with cyberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Unless otherwise specified, all participants responded on a 5-point Likert scale. Based on previous similar studies [ 38 , 39 , 40 , 41 ], we treated the 5-point scale with parametric tests.…”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise specified, all participants responded on a 5-point Likert scale. Based on previous similar studies [ 38 , 39 , 40 , 41 ], we treated the 5-point scale with parametric tests.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have proposed that, in the case of adolescents, they may experience physical somatization as a response to stress generated by family dysfunction linked to suboptimal (poorly organized or insecure) attachment styles. Such somatization may promote online health searches, which may generate or worsen cyberchondria [ 39 ]. Likewise, it has been suggested that insecure attachment styles may be associated with needs for control and intolerance to uncertainty, so these individuals may show poorer coping strategies to deal with uncertainty [ 40 ].…”
Section: Cyberchondriamentioning
confidence: 99%
“…While cyberchondria has been sparsely investigated in child and adolescent samples, young people are likely to be particularly susceptible to cyberchondria, given the massive role that the internet plays in many young people's lives (Alpaslan, 2016). Accordingly, recent findings based on a large sample of Chinese adolescents aged 12-20 years found health anxiety and cyberchondria to be tightly linked (Liu, Yang, Cheng, & Miao, 2022). However, a recent meta-analysis of university student samples indicates that the trend of increasing health anxiety started even before the inception of the Internet, speaking against cyberchondria as the only or main reason behind insidious health anxiety in society (Kosic, Lindholm, J€ arvholm, Hedman-Lagerl€ of, & Axelsson, 2020).…”
Section: Societal Consequences and Influencesmentioning
confidence: 99%